A Sustainable and Antimicrobial Food Packaging Film for Potential Application in Fresh Produce Packaging - An, Ling; Hu, Xinzhong; Perkins, Phil; Ren, Tian (Frontiers in Nutrition, 2022)
N-halamines are a group of compounds containing one or more nitrogen-halogen covalent bond(s). This high-energy halide bond provides a strong oxidative state so that it is able to inactivate microorganisms effectively. In this study, a sustainable film was developed based on polylactic acid (PLA) with incorporated N-halamine compound 1-chloro-2,2,5,5-tetramethyl-4-imidazolidinone (MC), as a promising antimicrobial food packaging material. Results showed that the incorporation of MC prevented the crystallization of PLA and improved the physical properties of the films. Additionally, both the moisture barrier and the oxygen permeability were improved with the presence of MC. Importantly, the antimicrobial film was able to inactivate inoculated microorganisms by a factor of seven log cycles in as little as 5 minutes of contact. Films that contained higher levels of MC further enhanced the antimicrobial efficacy. Fresh strawberries packed with the fabricated films maintained the quality up to 5 days. Due to the ease of fabrication and the effective biocidal property, these films have a wide range of potential applications in the field of food packaging to extend the shelf life of fresh produce.